Exploring water hyacinth (Eichhornia crassipes) as a cultivation substrate for oyster mushroom (Pleurotus species) production - Madhusudhanan, K; Aneesh, M M; Aneesh, P K; Kumar, PK Aneesh (Mushroom Research, 2015)
Please see the full text